Study of the salinity effects on the cooling and desalination performance of an adsorption cooling cum desalination system with a novel composite adsorbent. (25th November 2020) - Bai, S.; Ho, T.C.; Ha, J.; An, A.K.; Tso, C.Y.
Graphical abstract: Highlights: A model of an adsorption cum desalination system was experimentally verified. Composite adsorbent having a high water uptake and thermal conductivity was used. Effects of salinity on desalination and cooling performance were investigated. An experimental specific cooling power of 490 W/kg for seawater was achieved. A specific daily water production of 18 m3/tonne adsorbent/day was achieved. Abstract: Adsorption cooling cum desalination systems can produce cooling effect and fresh water simultaneously, powered by low-grade heat sources. This study aims to obtain the relationship between saltwater salinity and the cooling and desalination performance, and to develop a comprehensive numerical model that can accurately predict the cooling and desalination performance of an adsorption desalination system, with the use of a novel composite adsorbent having a high water uptake and thermal conductivity. A mathematical model has been developed, considering mass recovery process, preheating/precooling process and the effect of salinity on the physical properties of saltwater, which is verified by experiments on a prototype adsorption desalination system. It turns out that the simulation results match well with the corresponding experiment results. Under the operating conditions with the desorption temperature at 85 °C and evaporation temperature at 14 °C, experiment results show that the specific cooling power and specific daily water production values are 490 W/kg and 18 m 3 /tonne adsorbent/day for seawater. The trend of cooling and desalination performance change vs. saltwater salinity is clearly reported. Both experiment and simulation results demonstrate that the adsorption cooling cum desalination system adopting the composite adsorbent has a great potential to sustainably provide fresh water and cooling effect.